Computational Modelling of the Rail Vehicle Multibody System Including Flexible Bodies - Jan Dizo; Miroslav Blatnicky; Blanka Skocilasova (Communications - Scientific letters of the University of Zilina, 2015)
Tools for computer simulations are widely used in the field of a rail vehicle design. These means of virtual reality allow to perform static analyses of rail vehicle parts and dynamic analyses of a rail vehicle multibody system. For static analyses the finite element methods are most commonly used while the multibody system analyses are used for analyses of the rail vehicle dynamics. This paper deals with an implementation of flexible bodies into the rail vehicle multibody system. The implementation of flexible bodies into the rail vehicle multibody system extends the using of simulations, especially for an assessment of an influence of flexible bodies on running properties of the rail vehicle.